2012
DOI: 10.1186/1746-1596-7-108
|View full text |Cite
|
Sign up to set email alerts
|

Pathological femoral fractures due to osteomalacia associated with adefovir dipivoxil treatment for hepatitis B: a case report

Abstract: We present a case of a 62-year-old man who underwent total hip arthroplasty for treatment of pathologic femoral neck fracture associated with adefovir dipivoxil-induced osteomalacia. He had a 13-month history of bone pain involving his shoulders, hips, and knee. He received adefovir dipivoxil for treatment of lamivudine-resistant hepatitis B virus infection for 5 years before the occurrence of femoral neck fracture. Orthopedic surgeons should be aware of osteomalacia and pathological hip fracture caused by dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
2
18
2
Order By: Relevance
“…Nephrotoxicity associated with high-dose ADV typically has a late onset ([6 months) [15]. The time to onset of low-dose ADV-induced FS, based on case reports, ranges from a few months to [5 years [4][5][6][7][8][9][10][11][12]. In our patient, it took more than 2 years before the tubulopathy became apparent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nephrotoxicity associated with high-dose ADV typically has a late onset ([6 months) [15]. The time to onset of low-dose ADV-induced FS, based on case reports, ranges from a few months to [5 years [4][5][6][7][8][9][10][11][12]. In our patient, it took more than 2 years before the tubulopathy became apparent.…”
Section: Discussionmentioning
confidence: 99%
“…From the series of case reports so far, the time to resolution after cessation of ADV ranged from a few weeks to months [4][5][6][7][8][9][10][11][12]. A previous trial with high-dose ADV treatment showed a median time to resolution of renal dysfunction of 15 weeks, with the nephrotoxicity failing to resolve completely at 41 weeks after onset in 16 % of the patients [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Tanaka and colleagues [18] reported a 62-year-old man that developed pathological femoral fractures due to osteomalacia after 5 years from the beginning of adefovir, without deficiency of vitamin D.…”
mentioning
confidence: 99%
“…While adefovir dipivoxil (ADV) effectively suppresses the hepatitis B virus, it can cause proximal renal tubular dysfunction leading to phosphate wasting [1,2]. The safety of low-dose ADV (a dose of 10 mg/day), which does not induce clinically significant nephrotoxicity, is well recognized, but a few cases of hypophosphatemic osteomalacia (HO) caused by low-dose ADV therapy have recently been reported [3][4][5][6].…”
mentioning
confidence: 99%